2019
DOI: 10.1377/hlthaff.2019.00021
|View full text |Cite
|
Sign up to set email alerts
|

Home And Community-Based Workforce For Patients With Serious Illness Requires Support To Meet Growing Needs

Abstract: Home health and personal care aides are one of the largest groups of health care workers in the US, with nearly three million people providing direct care for people with serious illness living in the community. These home care workers face challenges in recruitment, training, retention, and regulation, and there is a lack of data and research to support evidence-based policy change. Personal care aides receive little formal training, and they experience low pay and a lack of respect for the skill required for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 23 publications
0
55
0
Order By: Relevance
“…Nurse aides are often described as special groups with low social status, lower education level, insu cient training, and poor wages. Other countries face the same problem [19] [21] [22] . Policies should be designed to ensure that nursing homes are adequately staffed and that infection control protocols are implemented with high quality [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Nurse aides are often described as special groups with low social status, lower education level, insu cient training, and poor wages. Other countries face the same problem [19] [21] [22] . Policies should be designed to ensure that nursing homes are adequately staffed and that infection control protocols are implemented with high quality [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Nurse aides are often described as special groups with low social status, lower education level, insu cient training, and poor wages. Other countries face the same problem [27,29,30]. Policies should be designed to ensure that nursing homes are adequately staffed and that infection control protocols are implemented with high quality [17].…”
Section: Discussionmentioning
confidence: 99%
“…According to these home care workers, appropriate delegation of care tasks would allow them to support clients who want to remain at home, and also would improve access to care by allowing nurses to focus on clients with the greatest needs (Bittner & Gravlin, 2009; Institute of Medicine, 2008). Expanded delegation of health maintenance tasks through the nurse practice acts, coupled with increased training opportunities for home care workers, may improve access to care in the home and be less costly (Spetz et al, 2019). For example, a pilot study in New Jersey revealed no adverse health outcomes, higher quality of life for consumers, and improved satisfaction among home health workers when nurses were authorized to delegate medication administration to certified home health aides (Young et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, if the client relies on an agency to employ an aide—whether with private funds or through Medicaid—the scope of practice of aides is controlled by state nurse practice acts. The nurse practice act can permit or prohibit licensed nurses from delegating health maintenance tasks to personal care aides and/or home health aides (Dower et al, 2013; Spetz et al, 2019). A study of delegation to home care workers conducted by AARP in 2016 found that 16 states allowed delegation of all 16 tasks inventoried, including feeding via gastrostomy tube, inserting suppositories, performing intermittent catheterization and ostomy care, administering oxygen therapy, and administering oral medications, insulin, intramuscular injection medications, enemas, and glucometer tests (AK, CO, ID, IA, KY, MN, MO, MT, NE, NM, NC, OR, TX, UT, VT, WA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation